Language-Games: Race and Bewitchment (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
This paper explores from a philosophical perspective the use of language describing matters concerning race and the possible implications of this for therapy. To do this, I shall consider Wittgenstein's philosophy of language and in particular, his 'language-game' methodology. I would like to examine the implications of the use of words, phrases and concepts which categorise on the basis of race, for example: 'black', 'white', 'Asian', 'mixed-race', 'the black community' and so forth, and to consider what assumptions lie therein, what purpose such descriptions serve and what problems they may create. It seems to me that such questions are of value within a therapeutic setting when matters of identity and belonging are concerned, especially in relation to so-called 'ethnic-minority' clients.
Keywords: Race; ethnicity; language; Wittgenstein; language-games; bewitchment; phenomenology